PERANCANGAN USER EXPERIENCE APLIKASI PETLYFE MENGGUNAKAN METODE DESIGN THINKING - Aulia, Firdias; Kusumaningtyas, Dian; Sardanto, Rino (Universitas Nusantara PGRI Kediri, 2022)
PetLyfe application is an application about digitizing medical records and pet care. The PetLyfe application helps solve user problems meeting the care and maintenance needs of pets. Therefore, designing the user experience of the PetLyfe application will help overcome these problems. This design process uses the design thinking method through five stages, namely empathize, define, ideate, prototype, and test. The design thinking method focuses on problem solving based on user experience and is effective for solving complex problems. Testing this research using the User Experience Questionnaire (UEQ) with the results of the attractiveness aspect value of 1.65 getting the good category, the perspicuity aspect value of 1.75 getting the good category, efficiency aspect (efficiency) 1.61 getting the good category. , the dependability aspect was 1.54 in the good category, the stimulation aspect was 1.74 in the excellent category, and the novelty aspect was 1.49 in the good category.